The work programme of NERIS in post-accident recovery. (October 2018) - Schneider, T.; Andronopoulos, S.; Camps, J.; Duranova, T.; Gallego, E.; Gering, F.; Isnard, O.; Maître, M.; Murith, C.; Oughton, D.; Raskob, W.
NERIS is the European platform on preparedness for nuclear and radiological emergency response and recovery. Created in 2010 with 57 organisations from 28 different countries, the objectives of the platform are to: improve the effectiveness and coherency of current approaches to preparedness; identify further development needs; improve 'know how' and technical expertise; and establish a forum for dialogue and methodological development. The NERIS Strategic Research Agenda is now structured with three main challenges: (i) radiological impact assessments during all phases of nuclear and radiological events; (ii) countermeasures and countermeasure strategies in emergency and recovery, decision support, and disaster informatics; and (iii) setting up a multi-faceted framework for preparedness for emergency response and recovery. The Fukushima accident has highlighted some key issues for further consideration in NERIS research activities, including: the importance of transparency of decision-making processes at local, regional, and national levels; the key role of access to environmental monitoring; the importance of dealing with uncertainties in assessment and management of the different phases of the accident; the use of modern social media in the exchange of information; the role of stakeholder involvement processes in both emergency and recovery situations; considerations of societal, ethical, and economic aspects; and the reinforcement of education and training for various actors. This paper emphasises the main issues at stake for NERIS for post-accident management.